Shirley Chisholm is a verb - Chambers, Veronica (Dial Books for Young Readers, 2020)
"A picture book biography celebrating the life and contributions of Shirley Chisholm, the first Black woman in Congress, who sought the Democratic nomination to be the president of the United States"--